Cost-effectiveness analyses comparing cemented, cementless, hybrid and reverse hybrid fixation in total hip arthroplasty: a systematic overview and critical appraisal of the current evidence. (4th July 2021) - Veldman, H.D.; de Bot, R.T.A.L.; Heyligers, I.C.; Boymans, T.A.E.J.; Hiligsmann, M.
ABSTRACT: Background : This study aims to present an overview and critical appraisal of all previous studies comparing costs and outcomes of the different modes of fixation in total hip arthroplasty (THA). A secondary aim is to provide conclusions regarding the most cost-effective mode of implant fixation per gender and age-specific population in THA, based on high quality studies. Methods : A systematic search was conducted to identify cost-effectiveness analyses (CEAs) comparing different modes of implant fixation in THA. Analysis of results was done with solely CEAs that had a high methodological quality. Results : A total of 12 relevant studies were identified and presented, of which 5 were considered to have the methodological rigor for inclusion in the analysis of results. These studies found that either cemented or hybrid fixation was the most cost-effective implant fixation mode for most age- and gender-specific subgroups. Conclusion : Currently available well performed CEAs generally support the use of cemented and hybrid fixation for all age-groups relevant for THA and both genders. However, these findings were mainly based on a single database and depended on assumptions made in the studies' methodology. Issues discussed in this paper have to be considered and future work is needed.